Long-term research impact: the case of adolescents having 'good places to spend free time' in Ireland. (20th October 2021) - Nic Gabhainn, S; Gavin, A; Kelly, C; Hanafin, S
Abstract: Background: Demonstrating long-term impacts of research can be fraught with methodological challenges, especially when approached retrospectively. Potential accusations of bias or over-interpretation, and a lack of clear and specific causal data, can be real obstacles. This paper presents a case study of research impact, including enablers and context to aid interpretation. To develop a national set of child wellbeing indicators in line with UNCRC commitments, a participative study of children's understandings of wellbeing was undertaken to accompany a Delphi study with experts. The children contributed a number of unique indicators, including having 'good places to spend free time'. Methods: Public actions which aimed to meet Irish commitments to child wellbeing were documented. Collected evidence comprised the development of, and reporting on, a national set of wellbeing indictors for children, the development and implementation of two national policies and cyclical monitoring data, collected through the nationally representative data sets of the Health Behaviour in School-aged Children (HBSC) study in Ireland, 2002-2018. Results: Measurement of stakeholder-informed indicators helped stimulate national policies on play (2004) and recreation (2007). Partnership-based policy implementation led to increases in spaces for play and recreation. Trends data from the HBSC study revealed significant and meaningful increases in 'good places to go spend free time' for children aged 10-17 from 45.1% in 2002 to 63.5% in 2018, and for all socio-demographic sub-groups. Temporal analyses showed that increases followed policy implementation. Conclusions: This impact case study links an original participative study, though policy development and implementation, to long-term improvements in Irish children reporting having 'good places to spend free time'. An understanding of the decision-making context at key points is important to aid interpretation of the evidence under investigation. Key messages: Commitment to child participation influenced national indicator adoption, policy development and implementation, with subsequent improvements to children's health-related environments. The quality and specificity of data needed to demonstrate long-term research impact is challenging and interpretation requires contextualisation to avoid leaps of faith.